2015
DOI: 10.1152/jn.00964.2014
|View full text |Cite
|
Sign up to set email alerts
|

Speech networks at rest and in action: interactions between functional brain networks controlling speech production

Abstract: Speech production is one of the most complex human behaviors. Although brain activation during speaking has been well investigated, our understanding of interactions between the brain regions and neural networks remains scarce. We combined seed-based interregional correlation analysis with graph theoretical analysis of functional MRI data during the resting state and sentence production in healthy subjects to investigate the interface and topology of functional networks originating from the key brain regions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 100 publications
(49 reference statements)
6
64
0
Order By: Relevance
“…We have demonstrated that phenotype‐ and genotype‐specific structural alterations characterized the clinical diversity of SD, potentially contributing to the pathophysiology of this disorder. As discussed below, these structural abnormalities were identified within the cortical sensorimotor network, as well as in white matter pathways of the speech production network …”
Section: Discussionmentioning
confidence: 95%
“…We have demonstrated that phenotype‐ and genotype‐specific structural alterations characterized the clinical diversity of SD, potentially contributing to the pathophysiology of this disorder. As discussed below, these structural abnormalities were identified within the cortical sensorimotor network, as well as in white matter pathways of the speech production network …”
Section: Discussionmentioning
confidence: 95%
“…The role of SMA in silent reading was especially interesting. Previous research has indicated some degree of functional connectivity between STC and SMA during speech and language tasks (Simonyan et al, ; Timmers et al, ), suggesting that SMA contributes to vocalization and syntax processing when syntax is difficult. But, we also found significant bidirectional connections between SMA and STC during the silent reading condition in which there was no vocalization.…”
Section: Discussionmentioning
confidence: 96%
“…Speech production is one of the most complex and unique human motor behaviors that dynamically engages over 100 orofacial, laryngeal and respiratory muscles. At the neural level, speech production is possible due to the orchestrated activation of multiple brain networks controlling sound perception, sensorimotor integration, and cognitive processing (Price, ; Fuertinger, Horwitz, & Simonyan, ; Simonyan & Fuertinger, ). A well‐known and long‐accepted hallmark of the organization of speech control is its left‐hemispheric dominance, which is known since the time of Broca (Strauss, Kosaka, & Wada, ; Frost et al, ; Hull & Vaid, ).…”
Section: Introductionmentioning
confidence: 99%